2016
DOI: 10.1371/journal.pone.0163344
|View full text |Cite
|
Sign up to set email alerts
|

Differing Alterations of Two Esca Associated Fungi, Phaeoacremonium aleophilum and Phaeomoniella chlamydospora on Transcriptomic Level, to Co-Cultured Vitis vinifera L. calli

Abstract: The filamentous fungi Phaeoacremonium aleophilum (P.al, Teleomorph: Togninia minima) and Phaeomoniella chlamydospora (P.ch) are believed to be causal agents of wood symptoms associated with the Esca associated young vine decline. The occurrence of these diseases is dramatically increasing in vineyards all over the world whereas efficient therapeutic strategies are lacking. Both fungi occupy the same ecological niche within the grapevine trunk. We found them predominantly within the xylem vessels and surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Comparative genomic studies suggested that pectinolytic enzymatic activity for breaking-down pectin-rich compounds such as tyloses walls and gels play a central role in the fitness of vascular wilts ( Klosterman et al, 2011 ). Previous reports confirmed that P. chlamydospora could metabolize pectin while possessing a limited ability to break down cellulo-lignified secondary cell walls ( Surico et al, 2001 ; Santos et al, 2006 ; Valtaud et al, 2009 ; Fischer et al, 2016 ). Computational analysis of the P. chlamydospora genome also supported these conclusions ( Antonielli et al, 2014 ; Morales-Cruz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 72%
“…Comparative genomic studies suggested that pectinolytic enzymatic activity for breaking-down pectin-rich compounds such as tyloses walls and gels play a central role in the fitness of vascular wilts ( Klosterman et al, 2011 ). Previous reports confirmed that P. chlamydospora could metabolize pectin while possessing a limited ability to break down cellulo-lignified secondary cell walls ( Surico et al, 2001 ; Santos et al, 2006 ; Valtaud et al, 2009 ; Fischer et al, 2016 ). Computational analysis of the P. chlamydospora genome also supported these conclusions ( Antonielli et al, 2014 ; Morales-Cruz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, apart from the extensive array of secondary metabolites in P. minimum, diverse virulence modes of action have been documented. These range from exopolysaccharides and polypeptides, causing varying degrees of disruption to water transport (10,84,85), to quinones and melanins, which shield the fungi against reactive oxygen species produced by plants as part of their defense mechanisms (10,(86)(87)(88). This suggests that changes in BGC gene content, and the corresponding secondary metabolites they produce, may be instrumental in adapting to new environmental conditions and could underlie a significant portion of intraspecific variations in virulence levels.…”
Section: Discussionmentioning
confidence: 99%
“…viticola challenge [ 7 , 9 ]. JA-mediated signaling has been associated with plant defense against necrotrophic pathogens and insects, inducing the accumulation of secondary metabolites and PR s; increased levels of phytoalexins and PR s is a common response of grapevine tissues to ESCA-associated fungi [ 5 , 33 , 35 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant response to pathogens is complex and composed of at least two layers: A basal, broad-band immunity called pathogen-associated molecular pattern-triggered immunity and a strain-specific level of immunity known as effector-triggered immunity. During the establishment of these immune responses, several compounds act as signals that trigger and mediate defense responses [ 5 , 6 , 7 , 8 , 9 ]. In general, the perception and communication of mechanisms triggered by each type of immunity are facilitated via Ca 2+ channels, mitogen-activated protein kinase (MAPK), nitric oxide (NO)-stimulated and reactive oxygen species (ROS)-regulated signaling cascades, which act as upstream sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation